Environmental Justice Framework Based on Local Wisdom Model - Imamulhadi, Imamulhadi; Idris, Idris; Nuriyah H., Eva (Faculty of Law Universitas Padjadjaran, 2024)
Indonesia's environmental justice system currently does not provide environmental law objectively. The philosophy, paradigm, approach, and objectives of environmental law as a regulatory basis are not applied by judges as intended by environmental law theories and concepts. This article aims to find an ideal environmental justice model. By applying a normative-empirical approach and a comparative method, as well as being based on qualitative juridical analysis, this article explores the values and principles contained in the local wisdom of indigenous communities that are relevant to becoming the basis for an environmental court model. This article concludes that the main problem that hampers environmental law enforcement at the court level is that the philosophy, paradigm, and methods of environmental law are marginalized due to the barriers of civil, criminal, and state administrative law regimes. The ideal environmental justice model is one that is based on the local wisdom values of indigenous communities, where environmental courts should be integrated, judged by certified competent judges, independent, and able to accommodate core environmental law theories and concepts.